Tightening Up? Impact of Musculoskeletal Ultrasound Disease Activity Assessment on Early Rheumatoid Arthritis Patients Treated Using a Treat to Target Strategy1. Issue 1 (January 2014) - Dale, James; Purves, David; McConnachie, Alex; McInnes, Iain; Porter, Duncan
<x xml:space="preserve">Abstract</x> Objective To determine the level of agreement and potential impact on disease‐modifying antirheumatic drug (DMARD) escalation decisions and of adding musculoskeletal ultrasound (MSUS) assessment of disease activity to the Disease Activity Score in 28 joints (DAS28) in early rheumatoid arthritis (RA). Methods Data were gathered from 53 early RA patients randomized to the MSUS assessment group of the Targeting Synovitis in Early Rheumatoid Arthritis study. DAS28 scores were calculated every month. MSUS was performed on patients with low disease activity (DAS28 <3.2) and on those with moderate disease activity (3.2 ≤ DAS28 <5.1) without clinically swollen joints (swollen joint count [SJC] ≤1). Fourteen joints (bilateral proximal interphalangeal joints 2 and 3, metacarpophalangeal [MCP] joints 2 and 3, the radiocarpal, and metatarsophalangeal joints 2 and 5) were examined. Active disease was defined as ≥2 joints demonstrating any power Doppler (PD) signal. Data from 414 paired DAS28 and MSUS assessments were pooled to determine the level of agreement between each method. Results A total of 369 MSUS assessments were conducted on patients with DAS28 <3.2; 92 (25%) of these assessments identified active disease. A total of 271 MSUS assessments were performed on those with DAS28 <2.6; 66 (24%) of these identified active disease. Forty‐five MSUS assessments were conducted on patients with 3.2 ≤ DAS28 <5.1 and SJC ≤1; 15 (33%) of these assessments confirmed active disease. On 120 occasions (29%), MSUS findings contradicted the DAS28 and led to modified treatment decisions. The joints that most frequently exhibited PD signal were radiocarpal and index and middle MCP joints. Conclusion Compared to the DAS28, global RA disease activity assessment using a limited MSUS joint set provided additional disease activity information and led to altered treatment decisions in a significant minority of occasions. This may allow further tailoring of DMARD therapy by supporting DMARD escalation in patients with continuing subclinical synovitis and preventing escalation in symptomatic patients with minimal clinical and/or ultrasonographic synovitis.